Book Review of Serving Gifted Students in Rural Settings by T. Stambaugh & S. Wood - Amie Price Azano (Journal of Research in Rural Education, 2017)
In the confl ated fi eld of rural gifted education, the very defi nitions of those two key terms can be political and elusive. The ways we defi ne rural and the context for rural education research have garnered debate and discussion at professional conferences and in formative works published in this journal (e.g., Arnold, Newman, Gaddy, & Dean, 2005; Coladarci, 2007; Howley, Theobald, & Howley, 2005). More often than not this discourse leads to questions of what is rural and what constitutes rural education. Similarly, in gifted education, parallel conversations on the nature of giftedness drive discussion and research. The edited collection Serving Gifted Students in Rural Settings makes a signifi cant contribution to the fi eld of rural gifted education by looking at these issues head on.